Review and modification of the valuation method of CN- with picric acid - Bosch Serrat, F. (Ars Pharmaceutica (Internet), 1968)
The analytical method based on the reaction of the ion -CN with pyridic acid for the investigation of the former is described with unequal success in some cases or completely ignored in other frequently used texts. However, we estimate that the method has interesting advantages over today's most widespread methods and that the modification we propose, using an alkaline pH regulated with NH4 + and NH3, makes it preferable the method of Aldridge's and the like in cases other than necessary a great sensitivity. Likewise, by the technique proposed, a previous distillation is made in a greater number of problems.